How can we study reasoning in the brain? - Papo, David (Frontiers in Human Neuroscience, 2015)
The brain did not develop a dedicated device for reasoning. This fact bears dramatic ‎consequences. While for perceptuo-motor functions neural activity is shaped by the input’s ‎statistical properties, and processing is carried out at high speed in hardwired spatially ‎segregated modules, in reasoning, neural activity is driven by internal dynamics and ‎processing times, stages, and functional brain geometry are largely unconstrained a priori. ‎Here, it is shown that the complex properties of spontaneous activity, which can be ignored ‎in a short-lived event-related world, become prominent at the long time scales of certain ‎forms of reasoning. It is argued that the neural correlates of reasoning ‎should in fact be ‎defined in terms of non-trivial generic properties of spontaneous brain activity, and that this ‎implies resorting to concepts, analytical tools, and ways of designing experiments that are‎‎ as ‎yet non-standard in cognitive neuroscience. The implications in terms of models of brain ‎activity, shape of the ‎neural correlates, methods of data analysis, observability of the ‎phenomenon and experimental designs are discussed.‎